Burnout to Breakthrough - McDargh, Eileen (Berrett-Koehler Publishers, 2020)
"Eileen delivers a new perspective on the burnout crisis with humor, good sense, and unique ideas on how to manage our brains. I owe my daily well-being to her. Keep this book at your side to help you glide through your workday." -Marcia Reynolds, PsyD, author of The Discomfort Zone It's official. For the first time, the World Health Organization has classified burnout as a health problem. Renowned motivational speaker Eileen McDargh proposes that to tackle it, we must learn to break out of energy-draining thoughts and behaviors. Resilience, she argues, is strictly a matter of energy management--by better managing your energy, you can both build resiliency and overcome burnout. Breakthrough happens when our energy is consciously distributed to what matters most in our lives. So after a short survey that will tell you where you fit in a burnout and resiliency profile, McDargh helps pinpoint the causes of your burnout and examine the energy demands that keep you from refueling and recharging. She provides an in-depth energy analysis and gives you the keys to master the four dimensions that can give you a resilience breakthrough: head, heart, hands, and humor. McDargh guides the reader through the process of identifying energy drains and implementing strategies for handling them, whatever phase of life you are in. Her intention is to help you not only to successfully manage work and life demands but also make even larger strides in understanding how to put together a life by design and not by default.